Pengaruh Jaipongan terhadap Seni Bangreng - Rustandi, Yuyus; Supriatna, R. Atang (Universitas Hamzanwadi, 2021)
In the Priangan area live and develop several types of dances. One of the diversities of dance types is one of them is the type of folk dance. Folk dance is a dance that has undergone development since primitive times, usually still very simple and attaches importance to the norms of beauty in standard form. West Java folk art with each other different forms, functions, and values. One of the interesting folk dances to research is bangreng art that lived and developed for decades in the Sumedang area. This research is intended as an effort to find out about the extent of Jaipongan's influence on Bangreng art. Based on many allegations that dance in Bangreng art is in the form of improvised movements, whereas Bangreng art has a specific pattern of motion and song. To get to know the art of Bangreng as a whole, research is needed to be revealed that Bangreng art is not the same as Jaipongan both dance, accompaniment, and the property used. To what extent Jaipongan's influence on the purity of Bangreng art needs to be expressed so that a picture of the changes concerning previous values is obtained.